Clade II Candida auris possess genomic structural variations related to an ancestral strain - Sekizuka, Tsuyoshi; Iguchi, Shigekazu; Umeyama, Takashi; Inamine, Yuba; Makimura, Koichi; Kuroda, Makoto; Miyazaki, Yoshitsugu; Kikuchi, Ken (PloS one, 2019)
Candida auris is an invasive and multidrug-resistant ascomycetous yeast that is under global surveillance. All clinical cases of C. auris infection diagnosed from 1997 to 2019 in Japan were non-invasive and sporadic otitis media cases. In the present study, we performed whole-genome sequencing of seven C. auris strains isolated from patients with otitis media in Japan, all of which belonged to clade II. Comparative genome analysis using the high-quality draft genome sequences JCM 15448T revealed that single nucleotide variations (SNVs), clade-specific accessory genes, and copy number variations (CNVs) were identified in each C. auris clade. A total of 61 genes involved in cell wall and stress response-related functions was absent in clade II, and the pattern of conserved CNVs in each clade was more stable in clade II than in other clades. Our data suggest that the genomic structural diversity is stable in C. auris isolated from each biogeographic location, and Japanese strains isolated from patients with otitis media might belong to an ancestral type of C. auris. One Japanese strain, TWCC 58362, with reduced susceptibility to fluconazole, exhibited no mutation in ergosterol biosynthesis-related genes (ERG). However, TWCC 58362-specific variations, including SNVs, indels, and CNVs were detected, suggesting that gene duplication events in C. auris might contribute to antifungal drug resistance. Taken together, we demonstrated that genomic structural variations in C. auris could correlate to geographical dissemination, epidemiology, lesions in the host, and antifungal resistance.